2020
DOI: 10.3390/jcm9092740
|View full text |Cite
|
Sign up to set email alerts
|

Targeting β2-Adrenergic Receptors Shows Therapeutical Benefits in Clear Cell Renal Cell Carcinoma from Von Hippel–Lindau Disease

Abstract: Von Hippel–Lindau (VHL), is a rare autosomal dominant inherited cancer in which the lack of VHL protein triggers the development of multisystemic tumors such us retinal hemangioblastomas (HB), CNS-HB, and clear cell renal cell carcinoma (ccRCC). ccRCC ranks third in terms of incidence and first in cause of death. Standard systemic therapies for VHL-ccRCC have shown limited response, with recurrent surgeries being the only effective treatment. Targeting of β2-adrenergic receptor (ADRB) has shown therapeutic ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 59 publications
4
18
0
Order By: Relevance
“…Zahalka et al showed that the loss of endothelial ADRB2 weaken angiogenesis in prostate cancer (20). However, other reports also indicated that β2-AR activation significantly suppressed tumor growth (15,(21)(22)(23)(24). Sakakitani et al (24) demonstrated that β2-AR agonist inhibited cell motility and induced mesenchymal-epithelial transition in oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Zahalka et al showed that the loss of endothelial ADRB2 weaken angiogenesis in prostate cancer (20). However, other reports also indicated that β2-AR activation significantly suppressed tumor growth (15,(21)(22)(23)(24). Sakakitani et al (24) demonstrated that β2-AR agonist inhibited cell motility and induced mesenchymal-epithelial transition in oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The current systemic therapeutic approaches include: targeting pathways of angiogenesis, immune checkpoint blockade, and mTOR inhibition. By inducing smooth muscle relaxation and vasodilation, these drugs are used for the treatment of hypertension (HTN) and obstructive symptoms associated with BPH (as discussed above) [216,217]. This mechanism of action is also utilized in the treatment of renal and ureteric stones, as α1 blockers reduce intraureteral pressure and increase fluid passage [216].…”
Section: Renal Cancermentioning
confidence: 99%
“…Doxazosin and naftodipil, selective α1-adrenoceptor antagonists, inhibit the proliferation of RCC cells both in vitro and in vivo human tumor xenografts in mice [47,213]. Propranolol induces loss of cell viability in RCC cells in vitro by increasing gene expression involved in apoptosis, decreasing HIF-α expression, and inhibiting the NFκB survival signaling [216,217]. α-1 blockade has been linked to an increased RCC incidence, although the study is limited by confounding factors such as concurrent BPH or HTN [224].…”
Section: Renal Cancermentioning
confidence: 99%
“…In addition, novel drugs have been developed based on the key pathways involved in HGB development, and their safety and effectiveness are being evaluated by several clinical studies (1,6,40,41). These medications include antiangiogenic agents, anti-VEGF agents, histone deacetylase inhibitors and inhibitors designed for HIFs (6,42,43). Among them, antiangiogenic agents were reported to halt tumor growth in RCC, and anti-VEGF agents may be more suitable for retinal HGBs and CNS HGBs (44)(45)(46).…”
Section: Treatmentmentioning
confidence: 99%